Acrylic adhesive composition
Patent Information
- Application Number
- JP2024110051
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-04-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing pressure-sensitive adhesive products lack balanced adhesion and cohesion, with some having satisfactory adhesive strength but inadequate cohesive strength, and vice versa.
A novel pressure-sensitive adhesive composition comprising 40-90% C6-C10 alkyl acrylate, 3-15% methyl (meth)acrylate, 0.1-5% ethylenically unsaturated compounds with keto or aldehyde groups, 0-2% ethylenically unsaturated acid, 0-30% other ethylenically unsaturated monomers, and a cross-linking reaction with a polyhydrazide compound having a di-functional group to enhance adhesion and cohesion.
The composition achieves improved adhesion and cohesion balance, resulting in enhanced peel strength and shear force resistance, suitable for applications in polymer packaging labels.
Abstract
Description
[Technical field]
[0001] The present disclosure relates to acrylic adhesive compositions, and in particular to acrylic pressure sensitive adhesive compositions.
[0002] Introduction In recent years, polymer packaging (e.g., polyethylene terephthalate (PET), High density polyethylene (HDPE), polyvinyl chloride (PVC), polypropylene (PP) or other plastic types) due to their light weight and good resistance to breakage. Pressure-sensitive film labels also increased in popularity over polymer packaging due to improved moisture resistance and appearance. Such packaging materials are increasingly being used in the food and beverage industry and can be recycled. The adhesive strength (peel properties) and cohesive strength (shear properties) are determined by the pressure-sensitive adhesive (PSA). In the prior art, there are several sensors with good adhesive strength. Pressure-sensitive adhesive products exist, but their cohesive strength is not satisfactory. Although there are some pressure sensitive adhesive products that have cohesive strength, their adhesive strength is not satisfactory. A pressure sensitive adhesive product that has a balance of adhesive and cohesive strength is desirable.
[0003] Thus, there are many applications in the art that require improved adhesive and / or cohesive strength or barrier properties. Alternative pressure sensitive adhesive compositions having desirable properties such as well-balanced adhesion and cohesion - Patents.com is strongly needed. Summary of the Invention
[0004] The present disclosure provides improved adhesive and / or cohesive strength, or balanced adhesion. The present invention provides novel pressure sensitive adhesive compositions having desirable properties such as strength and cohesion.
[0005] In a first aspect, the present disclosure provides a method for producing a pharmaceutical composition comprising: A) (a) 40-90% by weight of C6-C 10 Alkyl acrylate, (b) 3 to 15% by weight of methyl (meth)acrylate; (c) 0.1 to 5% by weight of ethylene having at least one keto or aldehyde group unsaturated compounds, (d) 0 to 2% by weight of an ethylenically unsaturated acid; (e) 0 to 30% by weight of other ethylenically unsaturated monomers and a polymer polymerized from a monomer mixture comprising (based on the total weight of the polymer mixture) B) At least two hydra groups react with keto or aldehyde groups via a cross-linking reaction. and a polyhydrazide compound having a dihydro functional group.
[0006] In a second aspect, the present disclosure provides a method for producing a PET film comprising: A) (a) 40-90% by weight of C6-C 10 Alkyl acrylate, (b) 3 to 15% by weight of methyl (meth)acrylate; (c) 0.1 to 5% by weight of ethylene having at least one keto or aldehyde group unsaturated compounds, (d) 0 to 2% by weight of an ethylenically unsaturated acid; (e) 0 to 30% by weight of other ethylenically unsaturated monomers and a polymer polymerized from a monomer mixture comprising (based on the total weight of the polymer mixture) B) At least two hydra groups react with keto or aldehyde groups via a cross-linking reaction. and a polyhydrazide compound having a dihydrogen functional group. An adhesive article is provided.
[0007] Both the foregoing general description and the following detailed description are exemplary and explanatory. It should be understood that the present invention is not limited to the disclosed embodiments, nor is it intended to be limiting of the invention as claimed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Unless otherwise defined, all technical and scientific terms used herein are It has the same meaning as commonly understood by a person skilled in the art to which the present invention belongs. All publications, patent applications, patents, and other references mentioned are incorporated by reference. Can be enjoyed.
[0009] As disclosed herein, the terms "composition," "formulation," or "mixture" are used herein to refer to any combination of The term refers to a mixture of different components obtained by simply mixing the different components together by physical means. Refers to the physical blend of
[0010] As disclosed herein, the term "glass transition temperature" (T g ) is used, for example, By various techniques, including differential scanning calorimetry (DSC) or calculation using the Fox equation It can be measured.
[0011] Throughout this document, the word fragment "(meth)acrylic" is interpreted as "methacrylic" For example, (meth)acrylic acid refers to both methacrylic acid and acrylic acid, and methyl (meth)acrylate refers to methyl methacrylate and (Meth)acrylamide refers to both methacrylamide and acrylamides. This refers to both the amides and the triamides.
[0012] An "aqueous" composition or dispersion herein refers to a composition in which particles are dispersed in an aqueous medium. In the present specification, the term "aqueous medium" refers to a mixture of water and a weight amount of water based on the weight of the medium. 0-30% by volume, e.g., alcohol, glycol, glycol ether, glyco By this term is meant water-miscible compound(s) such as diol esters and the like.
[0013] The present disclosure relates to A) (a) 40-90% by weight of C6-C 10 Alkyl acrylate, (b) 3 to 15% by weight of methyl (meth)acrylate; (c) 0.1 to 5% by weight of ethylene having at least one keto or aldehyde group unsaturated compounds, (d) 0 to 2% by weight of an ethylenically unsaturated acid; (e) 0 to 30% by weight of other ethylenically unsaturated monomers and a polymer polymerized from a monomer mixture comprising (based on the total weight of the polymer mixture) B) At least two hydra groups react with keto or aldehyde groups via a cross-linking reaction. and a polyhydrazide compound having a dihydro functional group.
[0014] Preferably, C6 to C 10 Alkyl acrylate is 2-ethylhexyl acrylate. acrylate and 2-propylheptyl acrylate. More preferably, 10 The alkyl acrylate is 2-ethylhexyl acrylate.
[0015] Preferably, the C6 to C6 10 The amount of alkyl acrylate (a) is 50% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, but not more than 90% by weight The content of the cellulose acetate solution may be 85% by weight or less, preferably 85% by weight or less, and more preferably 80% by weight or less. For example, C6~C 10 The amount of alkyl acrylate is 65-90% by weight of the monomer mixture. be.
[0016] The monomer methyl (meth)acrylate (b) is methyl acrylate and / or or methyl methacrylate.
[0017] Preferably, the amount of methyl (meth)acrylate (b) in the monomer mixture is 3 wt. % or more, preferably 4% by weight or more, more preferably 5% by weight or more, and even more preferably 6% by weight or more, even more preferably 8% by weight or more, but 15% by weight or less, preferably is 13% by weight or less, more preferably 12% by weight or less, and even more preferably 11% by weight or less. and even more preferably 10% by weight or less.
[0018] The ethylenically unsaturated compound (c) having at least one keto or aldehyde group is For example, acrolein, methacrolein, 1 to 20 in the alkyl radical, preferably Vinyl alkyl ketones having 1 to 10 carbon atoms, formyl styrene, alkyl One or two keto or aldehyde radicals or one aldehyde and one and (meth)acrylic acid alkyl ester having two keto groups, the alkyl radical being Preferably, they contain a total of 3 to 10 carbon atoms, examples of which are described in DE-A 2722097. Further, the (meth)acryloyloxyalkyl propanal is as described in For example, U.S. Pat. No. 4,228,007, DE-A 2061213 or DE-A22 Also preferred are N-oxoalkyl(meth)acrylamides such as those known from US Pat. No. 07209. It is appropriate.
[0019] Particularly preferred are acetoacetyl (meth)acrylate and acetoacetoxyethyl ( meth)acrylates, and in particular diacetone acrylamide (DAAM).
[0020] The amount of monomer (c) in the monomer mixture is 0.1 to 5% by weight, preferably 0.1 to 5% by weight. The content is 2% by weight, and more preferably 0.2 to 1% by weight.
[0021] The ethylenically unsaturated acid (d) is a sulfonic acid, a phosphoric acid, or, preferably, a carboxylic acid. Suitable examples include maleic acid, fumaric acid and itaconic acid, or preferably Examples of the acrylic acid include acrylic acid and / or methacrylic acid. The saturated acid (d) is acrylic acid.
[0022] Preferably, the amount of ethylenically unsaturated acid (d) in the monomer mixture is 0.1% by weight or less. Preferably, the content is 0.15% by weight or more, more preferably 0.20% by weight or more, and even more preferably It is preferably 0.25% by weight or more, but 5% by weight or less, more preferably 4% by weight or less, and even more preferably More preferably, the amount is 3% by weight or less, even more preferably, the amount is 2% by weight or less, and even more preferably, the amount is 1% by weight or less. The amount may be % or less.
[0023] The other ethylenically unsaturated monomers (e) may be of any type. For monomer (a) or monomer (b), C1 to C 18 Alkyl (meth)acryl Examples of the monomers include acrylates, (meth)acrylamides, vinyl aromatic compounds, or phosphorus-functional monomers. C1-C other than monomer (a) or monomer (b) 18 Alkyl (meth)acryl Preferred examples of the acrylate include ethyl acrylate, n-butyl acrylate, and n Preferred examples of vinyl aromatic compounds include styrene. Phosphorus-functional monomers include phosphoethylene and alpha-methylstyrene. Phosphopropyl (meth)acrylate, Phosphobutyl (meth)acrylate Phosphorus-containing (meth)acrylates, such as acrylates, their salts, and mixtures thereof SIPOMER PAM-100, SIP OMER PAM-200, SIPOMER PAM-300, etc. (R)-C(O)-O-(RO) n -P(O)(OH)2 (wherein R=H or CH3 , R1=alkyl, and n=2 to 6); phosphoethylene glycol (meth)acrylate , phosphodiethylene glycol (meth)acrylate, phosphotriethylene glycol ( (meth)acrylate, phosphopropylene glycol (meth)acrylate, phosphodipropylene Pyrene glycol (meth)acrylate, phosphotripropylene glycol (meth)acrylate Phosphoalkoxy(meth)acrylates, salts thereof, and the like; It may be a mixture of.
[0024] The amount of ethyl acrylate may be 10 to 30% by weight. The amount of ethyl acrylate in the mixture is 10% by weight or more, 12% by weight or more, or 15% by weight or more. , 16% by weight or more, but 30% by weight or less, preferably 25% by weight or less, more preferably 2 0% by weight or less. More preferably, the amount of ethyl acrylate is 15 to 20% by weight. %.
[0025] The amount of phosphorus-functional monomer may be from 0.01 to 2% by weight. The amount of phosphorus-functional monomer in the mixture is at least 0.02% by weight, at least 0.04% by weight, at least 0. 0.06% by weight or more, 0.08% by weight or more, but 2% by weight or less, preferably 1% by weight or less, more preferably More preferably, it may be 0.5% by weight or less, and even more preferably, it may be 0.3% by weight or less. Alternatively, the amount of the phosphorus-functional monomer is 0.06 to 0.3% by weight.
[0026] The amount of (meth)acrylamide is 0.01% by weight or more, preferably 0.05% by weight or more. , more preferably 0.10% by weight or more, and even more preferably 0.15% by weight or more, 4% by weight or less, preferably 3% by weight or less, more preferably 2% by weight or less, even more preferably Or it may be 1% by weight or less, and even more preferably 0.5% by weight or less.
[0027] In a preferred embodiment, the polymer A) is prepared by emulsion polymerization. , and is therefore an emulsion polymer.
[0028] In the case of emulsion polymerization, a suitable surfactant system and / or protective colloid, Or use a stabilizer.
[0029] Examples of suitable surfactant systems are known in the art and include anionic, These include nonionic, cationic, or amphoteric emulsifiers, and mixtures thereof. Examples of carboxylic surfactants are alkyl sulfates, ethoxylated alcohol sulfates, etc. Phosphates, aryl sulfonates, phosphates of ethoxylated alcohols, sulfosaccharides cyanates, sulfates and sulfonates of ethoxylated alkylphenols, and Examples of nonionic surfactants include, but are not limited to, and mixtures thereof. These include ethoxylated alcohols, ethoxylated alkylphenols, and mixtures thereof. Examples of cationic surfactants include, but are not limited to, ethoxylated and ethyl ketones. Exemplary surfactants include, but are not limited to, hydroxylated fatty amines. is 0.1 to 5.0% by weight, more preferably 0.3 to 5. 0% by weight, and most preferably 0.5 to 3.0% by weight. The surfactant is well known in the art. In one embodiment, the PSA is prepared by the following known conventional methods: The process involves emulsion of the monomer mix with a surfactant system prior to the polymerization reaction. This includes the
[0030] Examples of trade names for surfactants are AEROSOL® A-102, Dispon il® FES77, Dowfax® 2A1, Abex® 25 35, and RHODACAL® DS-4.
[0031] Water-soluble initiators for emulsion polymerization are, for example, ammonium peroxodisulfate. salts and alkali metal salts, e.g., sodium peroxodisulfate, ammonium persulfate , hydrogen peroxide, or an organic peroxide, such as tert-butyl hydroperoxide. do.
[0032] Also suitable are what are known as reduction-oxidation (redox) initiator systems.
[0033] A redox initiator system consists of at least one reducing agent, usually inorganic, and one organic Or it is composed of an inorganic oxidizing agent.
[0034] The oxidizing component includes, for example, an emulsion polymerization initiator as already mentioned above.
[0035] The reducing component is, for example, a sulfite such as sodium sulfite or sodium hydrogen sulfite. Alkali metal salts of disulfite, such as sodium disulfite, acetone disulfite Bisulfite adducts with aliphatic aldehydes and ketones, such as sulfates, or hydrochlorides. The solvent may include a reducing agent such as xymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems are soluble metals whose metal components can exist in multiple valence states. It can be used in conjunction with a metal compound.
[0036] An example of a common redox initiator system is ascorbic acid / iron(II) sulfate / peroxide. Sodium xanthate, sodium tert-butyl hydroperoxide / sodium disulfate, and and tert-butyl hydroperoxide / Na hydroxymethanesulfinate. The individual components, e.g. the reducing component, may be a mixture, e.g. hydroxymethanesulfinic acid and sodium disulfite.
[0037] These compounds are mostly used in the form of aqueous solutions, and low concentrations are tolerated in dispersions. The concentration is determined by the amount of water present, and the high concentration is determined by the solubility of each compound in water. The concentration is generally 0.1 to 30% by weight, preferably 0.5 to 20% by weight, based on the solution. Particularly preferably, the content is 1.0 to 10% by weight.
[0038] The amount of the initiator is generally 0.1 to 10% by weight, preferably 0.1 to 10% by weight, based on the monomer to be polymerized. The ratio is usually 0.3 to 5% by weight. The use of two or more different initiators in emulsion polymerization It is also possible.
[0039] The emulsion polymerization is generally carried out at a temperature of 30 to 130°C, preferably 60 to 95°C. The polymerization medium can be either water alone or a mixture of water and a water-miscible liquid such as methanol. Preferably, only water is used. Emulsion polymerization is a batch process. The process may be carried out as a batch process or in the form of a feed process, including a stepwise or gradient process. A portion of the polymerization mixture is introduced as an initial charge and heated to the polymerization temperature. Polymerization of the charge is initiated and then the remainder of the polymerization mixture is poured into, usually two or more spatially separated Feed streams, one or more of which may contain monomer either neat or in emulsified form The addition of the amine to the polymerization zone may be continuous, stepwise, or in a concentration gradient. and polymerization is maintained during this addition. To more effectively control the polymerization, polymer seeds may also be included in the initial charge. It is Noh.
[0040] In the process of free radical aqueous emulsion polymerization, how to add initiator to the polymerization vessel? The initiator is generally contained in the initial charge to the polymerization vessel. Depending on the rate at which it is consumed during free radical aqueous emulsion polymerization, In each particular case, the initiator is introduced either continuously or stepwise. In this case, this will depend on both the chemical nature of the initiator system and the polymerization temperature. The initiator is partially contained in the initial charge, and the remainder is added to the polymerization zone depending on the rate at which the initiator is consumed. It is preferable to supply the
[0041] To remove residual monomers, after the end of the actual emulsion polymerization, i.e., after a small amount of It is common to also add initiator after at least 95% monomer conversion.
[0042] In the feed process, the individual components are fed into the reactor from the top, the side, or the bottom. It can be added to the reactor through the bed.
[0043] In the case of emulsion polymerization, the amount is generally 15 to 75% by weight, preferably 40 to 75% by weight. An aqueous polymer dispersion having a solids content is obtained.
[0044] For a high space / time yield in the reactor, a dispersion with as high a solids content as possible is preferred. To be able to achieve a solids content of more than 60% by weight, it is preferable to have a bimodal or multimodal particle size. should be adjusted accordingly, otherwise the viscosity will be too high and the The dispersion can no longer be handled. The generation of new particles occurs, for example, when the seed (EP81083), by adding excess emulsifiers, or by using miniemulsions. Another advantage associated with low viscosity at high solids is that The formation of one or more new particles occurs at any one time. It is possible, guided by the particle size distribution targeted at low viscosity.
[0045] The polymer thus prepared is preferably used in the form of its aqueous dispersion. .
[0046] The pH of the polymer dispersion is preferably adjusted to a pH above 4.5, in particular to a pH between 5 and 9. It will be shortened.
[0047] The glass transition temperature of the polymer or polymers is preferably −60 to −30° C., particularly preferably The temperature is preferably from -55 to -30°C, and particularly preferably from -50 to -35°C.
[0048] The glass transition temperature can be determined by conventional methods such as differential thermal analysis or differential scanning calorimetry. (See, for example, ASTM 3418 / 82, Midpoint Temperature).
[0049] Compound B) is a polyhydrazide compound having at least two hydrazide functional groups. Specific examples of polyhydrazide compounds include oxalic acid dihydrazide, malonic acid dihydrazide, hydrazide, succinic dihydrazide, glutaric dihydrazide; adipic dihydrazide, Sebacic acid dihydrazide; Maleic acid dihydrazide, Fumaric acid dihydrazide, Itaconic acid Monoolefinic unsaturated dicarboxylic acid dihydrazides, such as dihydrazides; Polyhydrazides such as phthalic acid dihydrazide, terephthalic acid dihydrazide Aromatic dihydrazides such as isophthalic dihydrazide; 1,2,4-butane trihydrazide; 1,1,4-Butanetricarbohydrazide, 1,2,5-Pentanetricarbohydrazide Carbohydrazide, 1,3,6-Hexanetricarbohydrazide, 1,3,7-Heptane Tricarbhydrazide, and I-hydroxy-1,2,4-butanetricarbohydrazide and mixtures or any subset thereof. In one embodiment, the polyhydrazide is, but is not limited to, adipic dihydrazide. dihydrazide, isophthalic dihydrazide, sebacic dihydrazide, bis-semicarbizide, and and mixtures thereof. In another embodiment, the polyhydrazide is adipic dihydrazide. It is.
[0050] An effective amount of polyhydrazide crosslinker is one having a ratio of hydrazine functional groups to at least one ketone functional group. or of the ketone or aldehyde functional group of an ethylenically unsaturated compound having an aldehyde group About 0.02 to about 5 equivalents per equivalent, or at least one keto or aryl group. of ketone or aldehyde functional groups in ethylenically unsaturated compounds containing aldehyde groups or about 0.1 to about 3 equivalents, or at least one keto or aldehyde group About 0.001 equivalent of ketone or aldehyde functional group of an ethylenically unsaturated compound having It is such that the amount is 0.2 to about 1 equivalent.
[0051] The polyhydrazide compound B) can be added at any point in the process. In an embodiment, it is added after the emulsion reaction.
[0052] The weight fraction of B) is preferably 0.05 to 2 parts by weight per 100 parts by weight of polymer A). Parts by weight, in particular 0.05 to 1 part by weight, very preferably 0.1 to 0.7 parts by weight, of the polymer It is more preferably 0.1 to 0.3 part by weight per 100 parts by weight of -A).
[0053] The polymer A) or an aqueous dispersion of the polymer is mixed in a simple manner with the compound B). The resulting mixture was stable upon storage.
[0054] Pressure sensitive adhesives (PSA) are made up of either polymer alone or polymer A) and compound B) in water. The polymer may be composed of a polymeric dispersion.
[0055] PSA contains further additives: thickeners, defoamers, wetting agents, mechanical stabilizers, pigments, fillers , freeze-thaw agents, neutralizing agents, plasticizers, tackifiers (tackifying resins), adhesion promoters, and the like Examples of tackifiers include rosin, as well as disproportionated or heterodispersed tackifiers thereof. Natural resins, such as derivatives formed by polymerization, dimerization and / or hydrogenation. These may be used in the form of their salts (e.g., salts with monovalent or polyvalent counterions (cations)). The ester may be present in its pure form (in its pure form) or, preferably, in its esterified form. The alcohols used can be monohydric or polyhydric. Examples are methanol, ethanediol, diol, Ethylene glycol, triethylene glycol, 1,2,3-propanethiol, and It is pentaerythritol.
[0056] Further, hydrocarbon resins, such as non-hydrogenated aliphatic C5 resins, hydrogenated aliphatic C5 resins, aromatic Aromatically modified C5 resins, terpene resins, hydrogenated C9 resins, and combinations thereof are also used. do.
[0057] Other compounds that are increasingly being used as tackifiers include poly(ethylene glycol) copolymers having low molecular weights. The polyacrylate preferably has a molecular weight of less than 30,000. In a preferred embodiment, the polyacrylate has a weight average molecular weight MW of at least 60% by weight. , in particular composed of at least 80% by weight of C1 to C8 alkyl (meth)acrylates .
[0058] The preferred tackifier is rosin, either natural or chemically modified. It is composed of ethynyl acid or its derivatives.
[0059] The amount of tackifier by weight is preferably 5 to 100 parts by weight per 100 parts by weight of polymer. The amount is preferably 10 to 50 parts by weight (solid / solid).
[0060] The PSA contains 0 to 5 weight percent of a thickener, based on the total weight of the adhesive composition. All individual values and subranges from 0 to 5 weight percent are included herein, For example, the weight percent of the neutralizing agent may be 0, 0.5, or 1 weight percent. The viscosity increasing agent may be present in an amount ranging from a low of one percent to an upper limit of 1, 3, or 5 weight percent. The Dow Chemical Company, Midland, Mi ACRYSOL™, UCAR™, and C, commercially available from chigan These include, but are not limited to, ELOSIZE™.
[0061] The PSA contains 0 to 2 weight percent of a neutralizing agent, based on the total weight of the adhesive composition. All individual values and subranges from 0 to 2 weight percent are included herein, For example, the weight percent of the neutralizing agent may be 0, 0.3, or 0.5 weight percent. The amount of the carboxylic acid may range from a lower limit of 0.5, 1, or 2 weight percent to an upper limit of 0.5, 1, or 2 weight percent. The additive typically controls the pH to provide stability to the formulated pressure sensitive adhesive composition. Examples of neutralizing agents include aqueous ammonia, aqueous amine solutions, and other aqueous solutions. These include, but are not limited to, inorganic salts.
[0062] PSA is used in the manufacture of labels, adhesive tapes or sheets, e.g. protective films, etc. Used to make self-adhesive articles.
[0063] Self-adhesive articles generally have a layer of adhesive applied to one or both sides, preferably to one side. The backing is made of a
[0064] The backing material can be, for example, paper, metal foil, and preferably biaxially or uniaxially oriented. Polyolefins including polyethylene and polypropylene, polyethylene terephthalate Polymers made from (PET), polyvinyl chloride (PVC), polystyrene or polyamide The film may include
[0065] The present disclosure relates to a self-adhesive adhesive comprising the backing material and the pressure sensitive adhesive composition disclosed herein. A pharmaceutical article is provided.
[0066] Conventionally coating the backing material to create an adhesive layer on the backing material. The usual coating amount is, for example, 5 to 50 g / m 2 (solid, no water).
[0067] The configured coated substrate may be, for example, a label, an adhesive tape or a sheet. , for example, as a self-adhesive article such as a protective film. The PSA-coated surface of the substrate, for example a label, is attached to a release paper such as silicone-treated paper. It can be covered with.
[0068] The self-adhesive articles of the present invention have good performance properties, particularly improved adhesive and cohesive strength. , and / or have an improved adhesive / cohesive balance. EXAMPLES
[0069] Some embodiments of the present invention are described herein in the following examples, all of which are incorporated herein by reference. and percentages are by weight unless otherwise specified. Raw materials: [Table 1]
[0070] Emulsion Polymerization Generally, an emulsion mixture according to the present disclosure is prepared as follows: , mechanical stirrer, temperature controlled thermocouple and inlets for initiator and monomer A 4 liter, 5-neck reactor equipped with a centrifuge was charged with 675 g of deionized ("DI") water and gently stirred. Heat to 88 °C under a gentle N2 flow. In a separate container, add 275 g DI water, 10 g RHODACAL DS-4, 12g AEROSOL A-102, 2.5g Na2 CO3, as well as 2-ethylhexyl acrylate ("2-EHA"), butyl acrylate Acrylate ("BA"), Ethyl Acrylate ("EA"), Methyl Methacrylate ("MMA "), acrylic acid ("AA"), AM, PEM, and / or DAAM. A monomer emulsion was prepared by mixing 1,672 g of a monomer mixture containing It is prepared.
[0071] Next, a mixture of Na2CO3 in 40 g of DI water and ammonium persulfate ("APS") was added. The mixture solution is added to the reactor. Immediately after adding the Na2CO3 and APS solutions, The monomer emulsion is fed to the reactor. The feeds are continued for 80 minutes.
[0072] After the addition of the monomer emulsion is complete, the reaction mixture is cooled to 60° C. and then cooled to t ert-Butyl hydroperoxide (70%) ("t-BHP") (32 g in DI water 9.2g), and 6.8g Bruggemann Chem in 34.5g DI water ical US Company, Chadds Ford, Pennsylvania A reducing agent solution such as BRUGGOLITE FF6 M ("FF6") from Add the mixture slowly through two separate pipes over a period of 10 minutes. Once the feeds are complete, allow the reaction to cool to room temperature. The resulting composition is then filtered through a 325 mesh filter cloth for subsequent evaluation. A composition for the evaluation run is prepared.
[0073] Pressure Sensitive Adhesive Formulation All samples were wettable due to laboratory drawdowns unless otherwise noted. Based on the entire emulsion, Evonik Industries has acquired Wetting agents such as 0.3% (wet / wet) Surfynol 420 wetting agent ("420") A small amount of lubricant is added. ADH is also added. Next, The Dow Chemical ACRYSOL RM-L Company, Midland, Michigan Use a thickener such as RM-2020 to increase the viscosity to approximately 600 cps (Br ookfield, RVDV, 30 rpm, 63#) and use ammonia, Adjust the final pH to 7.0-7.5.
[0074] Laboratory Drawdown Laminated with polypropylene ("PP") film (thickness 60 micrometers) The adhesive is pretreated by corona treatment before processing. The compounded adhesive is applied at a dry weight of 17 g / m 2 The PE film is coated with 40p of the adhesive and dried at 105°C for 2 minutes. Laminate with a release liner coated with a pressure-sensitive adhesive at 40°C under pressure of 1000 psi. do.
[0075] Application Test Performance testing was performed by subjecting the adhesive laminate to a controlled environment (22-24°C, relative humidity 50- 60%) testing can be performed in a laboratory after 5 days of conditioning.
[0076] Peel Strength Test: Glass Test Plate and High Density Polyethylene (HDPE) Test Plate Peel strength testing at 90° for both sheets was according to FINAT test method No. 1. Before testing, the sample strips (formulated without wax) were placed on the test plate for 20 minutes and The patch was applied for a 1-day residence time.
[0077] Cohesion / shear test: The shear resistance test against a glass test plate is carried out using the FINAT test Use test method No. 8.
[0078] The failure mode is recorded after the test value: "AF" indicates adhesive failure and "AFB" indicates adhesive failure from the backing, "MF" indicates mixed failure, and "CF" indicates cohesive failure. Illustrative Examples ("IE") and Comparative Examples ("CE") are detailed in Table 1 below. Table 1 details the formulation and PSA properties of the compositions of Examples IE and CE. It is listed. [Table 2]
[0079] Compared to compound CE1, compounds IE1-IE5 had better HDPE peel. The IE1, IE2 and IE5 formulations showed better 1-day glass peeling. The shear strength performance of IE1 to IE5 was adhesive failure, which is because the cohesive strength was stronger than the adhesive strength. The IE3 and IE4 formulations showed good shear strength over 200 hours. A shear strength was obtained which was much better than CE1 and CE2.
[0080] Compared to the CE2 formulation, the IE5 formulation experienced higher shear forces and slightly Low HDPE peel was obtained. Glass peel after 1 day was comparable.
[0081] Compared to the formulation CE3, which contains 30% EHA in the monomer mixture, IE1 to IE Formulation 5 gave much better shear properties.
[0082] If the EA content of the monomer mixture is too high, the Tg will be too high. If the MMA content of the polymer is too high, the Tg will be too high. It can increase the stiffness of the adhesive, decrease its wettability, and reduce its adhesive properties. The polymers are sufficiently bonded to provide adequate pressure sensitive adhesion, especially on surfaces with low surface energy. Not compatible.
[0083] Compared to formulations CE3 and CE4, formulation IE4 showed significantly better shear strength, And the same or better adhesion was obtained on both glass and HDPE. CE6 was good. The CE7 had adequate adhesion but too low shear performance (cohesion), whereas the CE8 had adequate adhesion but too low shear performance (cohesion). Although a sufficient shear strength was obtained, the adhesive strength was lower than that of all of the examples IE1 to IE5 of the present invention. Both CE6 and CE7 have a better adhesive / cohesive balance than the inventive examples. Inferior.
Claims
[Claim 1] A) (a) 40 to 90% by weight of C 6 ~C 10 Alkyl acrylate, (b) 3 to 15 weight percent methyl (meth)acrylate; (c) 0.1 to 5 weight percent of an ethylenically unsaturated compound having at least one keto or aldehyde group; (d) 0 to 2 weight percent of an ethylenically unsaturated acid; (e) 0 to 30% by weight of other ethylenically unsaturated monomers, and (f) (meth)acrylamide a polymer polymerized from a monomer mixture comprising: B) a polyhydrazide compound having at least two hydrazide functional groups that react with said keto or aldehyde groups by a crosslinking reaction; 1. A pressure sensitive adhesive composition comprising: